Myrtaceae Juss.: a review of historical context, biogeographical distribution, ethnobotanical and ethnopharmacological aspects - Lucas Tenório, Camylla Janiele; Barbosa Machado, Janaina Carla; Assunção Ferreira, Magda Rhayanny; Lira Soares, Luiz Alberto (Ethnobotany Research and Applications, 2026)
Background: The Myrtaceae family is a taxonomically rich and widely distributed group of plants occurring predominantly in tropical and subtropical regions, extensively used in traditional medicine and recognized for its strong ethnopharmacological relevance across diverse cultural contexts. This review integrates historical, taxonomic, biogeographical, ethnobotanical, and ethnopharmacological knowledge to identify use patterns, centers of diversity, and knowledge gaps limiting sustainable valorization Methods: A stepwise literature review was conducted using PubMed, Scopus, Wiley, ScienceDirect, and Google Scholar, complemented by Flora do Brasil, Flora of Australia, GBIF, and Plants of the World Online. Ethnobotanical and ethnopharmacological studies were systematically selected based on formal botanical identification supported by voucher specimens. Publications were screened and analyzed to compile data on plant parts used, preparation methods, therapeutic indications, geographic distribution, and associated biological activities Results: Psidium guajava, Syzygium spp., Eucalyptus spp., and Eugenia spp. were the most cited taxa. South America and Australia emerged as major centers of diversity, although Asia and Africa also stand out due to the high number of ethnobotanical studies. Leaves were the most frequently used plant part, mainly prepared as decoctions or infusions and administered orally. The main indications included gastrointestinal, respiratory, inflammatory, and infectious conditions. Available evidence partially supports traditional uses, especially antimicrobial and anti-inflammatory activities. Conclusions: Despite its ethnopharmacological relevance, gaps in taxonomic standardization and sustainable valorization persist, highlighting the need for more integrative and methodologically consistent approaches to support conservation and innovation. Keywords: Ethnopharmacology, ethnobotanic, Eugenia, Folk medicine, Psidium, Syzygium.